Effective time duration of Chinese electronic fly catcher trap bait on the best performance - Saiful Bahri, Mohamed; Rokiah, Zainuddin (2017)
Chinese Electronic Fly Catcher Trap (CEFCT) baits are found to be the most effective baits used in attracting flies in Malaysia as has been proved by previous studies. The manufacturer of this bait failed to reveal the material components for this bait, which thus, precludes other researchers attempt to reinvent baits that are have imitates such effects as CEFCT bait. It is necessary for researchers to investigate the phenomenon why this bait remains the best bait due to a major challenge in identifying effectiveness of time duration in this bait because of some factors. It was revealed that this bait is very expensive and the supply of this bait in market is quite less. Hence, this makes this research more significantly invaluable because the researchers identify the factors that makes CEFCT bait as the most effective in attracting flies in terms of bait performance. Chemometric analysis (cluster analysis CA & discriminant analysis DA) and spread plate bacteria analysis on Nutrien Agar (NA) were carried out in order to determine the effective time duration for the best performance of the bait. Chemometric analysis was conducted by running eight sample of CEFCT baits using Gas Chromatography Mass Spectrum (GC-MS). Furthermore, for spread plate bacteria count analysis, eight samples of CEFCT bait were prepared with different solution combinations. It was plate on NA agar and bacteria that were counted on day 2, 3 and 4 only. Each time effective analysis was run by using eight discriminant variables: 30 minutes, 2 hours, 4 hours, 6 hours, 8 hours, 12 hours, control CEFCT powder, and control molasses (p < 0.05). Therefore, it was observed that the CEFCT bait bioassays analysis shows that CEFCT baits were very active up to 30 minutes through CFU count in day two until day four (9.28, 9.34, and 9.35 lofcfu/ml). Although, for Chemometrix analysis, CEFCT bait can achieve its time effectiveness through CA and DA according to three group of time effectiveness given by correct classification (100%, 75%, and 75%). The results indicated that chemometric techniques can be used for rapid assessment of time duration of CEFCT bait. Further researches are needed to identify low-cost bait components with similar effect of the best bait (CEFCT) in local markets in order to develop new low cost baits.